On the use of bolus for pacemaker dose measurement and reduction in radiation therapy. (20th November 2017) - Yan, Huagang; Guo, Fanqing; Zhu, Dengsong; Stryker, Stefan; Trumpore, Sharron; Roberts, Kenneth; Higgins, Susan; Nath, Ravinder; Chen, Zhe; Liu, Wu
Abstract: Special attention is required in planning and administering radiation therapy to patients with cardiac implantable electronic devices (CIEDs), such as pacemaker and defibrillator. The range of dose to CIEDs that can induce malfunction is large among CIEDs. Clinically significant defects have been reported at dose as low as 0.15 Gy. Therefore, accurate estimation of dose to CIED and dose reduction are both important even if the dose is expected to be less than the often‐used 2‐Gy limit. We investigated the use of bolus in in vivo dosimetry for CIEDs. Solid water phantom measurements of out‐of‐field dose for a 6‐MV beam were performed using parallel plate chamber with and without 1‐ to 2‐cm bolus covering the chamber. In vivo dosimetry at skin surface above the CIED was performed with and without bolus covering the CIED for three patients with the CIED <5 cm from the field edge. Chamber measured dose at depth ~0.5–1.5 cm below the skin surface, where the CIED is normally located, was reduced by ~7–48% with bolus. The dose reduction became smaller at deeper depths and with smaller field size. In vivo dosimetry at skin surface also indicated ~20%–60% lower dose when using bolus for the three patients. The dose measured with bolus more accurately reflects the dose to CIED and is less affected by contaminant electrons and linac head scatter. In general, the treatment planning system (TPS) calculation underestimated the dose to CIED, but it predicts the CIED dose more accurately when bolus is used. We recommend the use of 1‐ to 2‐cm bolus to cover the CIED during in vivo CIED dose measurements for more accurate CIED dose estimation. If the CIED is placed <2 cm in depth and its dose is mainly from anterior beams, we recommend using the bolus during the entire course of radiation delivery to reduce the dose to CIED.